Adaptive Landscape by Environment Interactions Dictate Evolutionary Dynamics in Models of Drug Resistance - Ogbunugafor, C. Brandon; Wylie, C. Scott; Diakite, Ibrahim; Weinreich, Daniel M.; Hartl, Daniel L. (PLOS Computational Biology, 2016)
Author Summary The adaptive landscape analogy describes the process of evolution by examining how individual mutations in a gene or genome affect the reproductive success of an organism. In certain cases, it can offer insight into what pathways evolution is likely to take in moving between different phenotypes. The analogy has been used by evolutionary biologists to describe a number of phenomena ranging from how mutations affect hemoglobin function to how bacteria evolve resistance to antibiotics. In this study, we combine computational biology with experimental data to examine how the environment—defined as the type of drugs and their amounts—affects the structure of adaptive landscapes for drug resistance in Plasmodium falciparum (the agent responsible for the most deadly form of malaria) with respect to mutations in dihydrofolate reductase (DHFR), an enzyme that plays an important role in drug resistance. We conclude that the environment has a profound effect on how the evolution of drug resistance occurs. In the future, these details should be integrated into models of antimicrobial therapy, as they greatly influence the dynamics of drug resistance evolution.